1998
DOI: 10.1111/j.1540-8167.1998.tb01836.x
|View full text |Cite
|
Sign up to set email alerts
|

Organized Activation During Atrial Fibrillation in Man

Abstract: An organized activation during atrial fibrillation with a predominant craniocaudal direction on the trabeculated right atrium is frequently present and influences the appearance of "coarse" or "fine" atrial fibrillation as well as F wave polarity on the surface ECG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Predictors of successful ablation: In the present study, the successful group had a significantly higher F wave amplitude in lead V1 than the unsuccessful group. Roithinger, et al 28) reported that a predominance of organized activation in the trabeculated right atrium influences the presence and polarity of surface F waves in lead V1.…”
Section: Discussionmentioning
confidence: 99%
“…Predictors of successful ablation: In the present study, the successful group had a significantly higher F wave amplitude in lead V1 than the unsuccessful group. Roithinger, et al 28) reported that a predominance of organized activation in the trabeculated right atrium influences the presence and polarity of surface F waves in lead V1.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques have been applied to Holter ECG recordings since only long recordings allow a detailed analysis of autonomic tone or rate control effects in the atrial and ventricular response during AF. Although the evaluation of global phenomenon rather than detailed analysis of the AV node zone could implicate some limitations, the assumption that DACL could be calculated from ECG signals was based on the demonstrated stable relation between rate of ECG atrial waves and endocardial cycle length [118]. Notice that only segments with an accurate estimation of the DACL were used for the comparison.…”
Section: Limitationsmentioning
confidence: 99%
“…For this reason, many research groups have focused in determining the atrial organization degree from the surface ECG given that spectral features of surface ECG recordings during AF have shown to be highly correlated with intracardiac measurements [108].…”
Section: Quantification Of the Temporal Organization Of Afmentioning
confidence: 99%
“…Analysis of the frequency content of AF signals on the body surface has been shown to be correlated with the analysis of the frequency content of electrograms [108,66]. This technique seems to be useful for monitoring and predicting response to therapy, such as antiarrhythmic drugs or cardioversion [11].…”
Section: Comparison With Non-invasive Studiesmentioning
confidence: 99%
See 1 more Smart Citation